The Relationship between Information Literacy and Information Overload on TikTok among Library and Information Science Students at Padang State University - Nadya Amalia; Gustina Erlianti (Darul Yasin Al Sys, 2026)
The rapid growth of social media has increased users’ exposure to excessive volumes of digital information, making information literacy essential for evaluating, organizing, and managing information effectively. However, the extent to which information literacy is associated with information overload in the context of TikTok use remains insufficiently understood. This study examined the relationship between information literacy and information overload among Library and Information Science students at Padang State University. A quantitative correlational design was employed, involving 78 students selected through simple random sampling. Data were collected using a structured questionnaire based on the SCONUL Information Literacy Model and the information overload framework developed by Bawden and Robinson. The data were analyzed using descriptive statistics, Pearson product–moment correlation, and the coefficient of determination. The findings showed that both students’ information literacy and information overload were at high levels. Nevertheless, information literacy was negatively but not significantly correlated with information overload (r = −0.126, p = 0.272), leading to the retention of the null hypothesis. Information literacy explained only 1.6% of the variance in information overload (R² = 0.016), indicating that students with strong information literacy competencies may still experience substantial information overload when using TikTok. The study concludes that information literacy alone is insufficient to explain students’ information overload in social media environments. These findings extend the literature on digital information behavior and provide a basis for investigating additional individual, technological, and contextual factors that may contribute to information overload among university students.